Efficacity of ternidazole-neomycin sulfate-nystatin and prednisolone association in syndromic management of vaginitis in low and middle incomes countries - Mian, Dehi Boston; Serges Loue, Vedi Andre; Angoi, Aya Virginie; Yao, Alexis; Sofia, Akinloye; guessan, Koffi N’; Boni, Serge (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Vaginitis is a frequent and treated based on clinical evaluation in our countries in absence of microbiological laboratories. Evaluate the effectiveness of the management of vaginitis by ternidazole, neomycin sulfate, nystatin, prednisolone association. Methods: A five-month prospective study was carried out in three health facilities in Abidjan. Two-hundred and thirty-three patients with clinical signs of vaginitis were included after signed consent. Pregnant and breast-feeding patients, hypersensitivity or idiosyncrasy to ternidazole, neomycin sulfate, nystatin, prednisolone association were not included. Patients were divided into reference group (n=200) for which a microbiological analysis of vaginal secretions was carried out 2-4 days before treatment and control group (n=33) for which treatment was initiated straightaway. Evaluation criteria were clinical symptoms, microbiological balance carried out 10 to 14 days after treatment and occurrence of side effects. Statistical tests used were Khi2 and exact Fisher test (p<0.05). Results: Pathological leucorrhoea was differently observed in both group (p=0.001). During the follow-up visit, the persistence of symptoms was not different (p=0.99). This combination has demonstrated its efficacy in cases of Candida albicans vaginitis, bacterial vaginosis, trichomonas vaginalis vaginitis, and mixed vaginitis. A significantly improvement of symptoms (p=0.001) and low rate of biologically proven recurrence was observed in both groups. No allergic reactions linked was reported. Conclusions: In our countries this therapeutic combination appears to be an option for treated mixed vaginitis in first intention without preliminary samples of vaginal secretions.